(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
Humanity witnessed a manifestation of different forms of violence throughout history. Violence has become the most serious phenomenon that threatens human existence, especially with the development of its techniques and technologies that have produced multiple facets of it with various levels, complexities and degrees of danger. This led to different opinions and views by philosophers who wrote about violence.. This paper discusses Marcuse’s criticism of contemporary industrial society that practices authoritarianism and violence on individuals, and eventually produces counter-violence that is justified and necessary for change and liberation from increased hidden repression used by advanced systems that employs technology, and that has a close relationship to existing controlling power. Therefore, there was a necessity to call for tolerance, but under certain conditions away from the repressive tolerance practiced by the controlling power. This research discusses this issue and clarifies the role of revolutionary violence in Marcuse’s writing in achieving liberation from suppression by the repressive power .